Law Enforcement The Crime Of Corruption Abuse Of School Operational Assistance Funds - Tri Syafari; Ridjal J Kotta; Basto Daeng Robo (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2021)
With the existence of school operational assistance funds (BOS), it is hoped that public access to quality education is expected can be achieved. However, in practice the use of BOS funds is not always what is expected. This is because there are irresponsible elements who often misuse the BOS funds. Individuals who use BOS funds not in accordance with the guidelines for the use of BOS funds can be held legally responsible. The occurrence of corruption in the misuse of school operational assistance funds is caused by several factors, namely the school operational assistance management team that should have been formed by the school principal has never been formed, so that the management of school operational assistance funds is not transparent and accountable. Another factor is the weakness of the control system in the management of the School Operational Assistance Fund, which creates opportunities for managers to use BOS funds for personal interests. Perpetrators of criminal acts of corruption misuse of school operational assistance funds have been processed by law enforcement officials. The process starts from the stages of investigation, prosecution and trial and has obtained a final and binding decision. Even the perpetrator who was convicted and has served the sentence imposed on him. In the process, law enforcement officers have carried out the law enforcement process and have provided legal certainty for the actions of the perpetrators. However, the results of the process are still far from the principles of justice and benefits for the community